Digital media-enhanced cultural brand development: creative strategies for urban identity construction - Wei, Zhang; Mastika, Lamat (Furture Publishing LLC, 2025)
This study investigates digital media-enhanced cultural brand development through creative strategies for urban identity construction, aiming to develop a comprehensive framework that extends integrated marketing communication theory while preserving cultural authenticity and enabling community participation. A mixed-methods approach incorporated stakeholder surveys (n=420) across four participant groups, systematic analysis of 800 social media posts, examination of 35 institutional platforms, and comparative analysis of 12 international cities, utilizing an AI-enhanced analytical pipeline with natural language processing, computer vision, and machine learning algorithms. Five core creative strategy elements were empirically validated: digital storytelling integration, community-centered content creation, heritage-digital synthesis, interactive cultural experiences, and dynamic community feedback systems. Community-centered content creation achieved the highest community acceptance correlation (r=0.91) and cultural authenticity correlation (r=0.84), while heritage-digital synthesis demonstrated the strongest urban identity impact correlation (r=0.88). Strategic digital media integration significantly amplifies urban cultural brand transmission effectiveness while preserving authentic cultural identity through community-centered approaches, providing urban administrators with evidence-based implementation frameworks for sustainable urban identity construction.